1992
DOI: 10.1152/ajpheart.1992.262.2.h391
|View full text |Cite
|
Sign up to set email alerts
|

Age-related response of rabbit heart to normothermic ischemia: a 31P-MRS study

Abstract: The age-related response of the myocardium to 30 min of 37 degrees C global ischemia and 120 min of 37 degrees C reperfusion, measured by phosphorus-31 magnetic resonance spectroscopy and the recovery of isovolumic function, was evaluated by using perfused neonatal (3-8 days old, n = 10), immature (24-30 days old, n = 10), and adult (2-4 mo old, n = 5) rabbit hearts. Basal intracellular pH (pHi) was highest in neonatal hearts and decreased with age. The basal phosphocreatine (PCr)-to-ATP ratio differed in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Although CCC decreased intracellular acidosis during isch emia in both age groups, during the last 20 min of ischemia the relationship between the age groups was reversed so pHj was greater in adult than in neonatal hearts. These results are similar to those of our previous study of ischemia alone which suggested that recovery of function during reperfusion is inversely related to the magnitude of the fall in pH| dur ing ischemia [3]. In the present study, preser vation of ATP during ischemia after CCC was followed by improved functional recovery in adult hearts.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although CCC decreased intracellular acidosis during isch emia in both age groups, during the last 20 min of ischemia the relationship between the age groups was reversed so pHj was greater in adult than in neonatal hearts. These results are similar to those of our previous study of ischemia alone which suggested that recovery of function during reperfusion is inversely related to the magnitude of the fall in pH| dur ing ischemia [3]. In the present study, preser vation of ATP during ischemia after CCC was followed by improved functional recovery in adult hearts.…”
Section: Discussionsupporting
confidence: 92%
“…These studies provide further evidence that PCr in neonatal rabbit hearts is less than that reported for older rabbit hearts [3,16,22,23,26,30,31]. Although the spectra used to generate our data were acquired from partial ly saturated Pi and PCr, our estimate of T1 for PCr of 2.2 sand the algorithm used by Carr et al [3] and Gadian et al [32] can be used to calculate control PCr/|3-ATP = 0.55, signifi cantly less than the value considered to be a minimum for control adult heart spectra [33].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations